Early development in neurogenetic disorders - Fidler, Deborah J. (International review of research in developmental disabilities, 2011)
This special issue is among the first volumes to examine the topic of early development in children with neurogenetic disorders associated with intellectual disability. It includes discussions of theoretical issues regarding the emergence of behavioural profiles during early development, as well as comprehensive accounts of early development in specific disorders such as Down syndrome, fragile X syndrome, Williams syndrome, and sex chromosome disorders. In addition, several contributions examine the latest clinical applications of this work for diagnosis, treatment, and education.